2014
DOI: 10.1097/imi.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Healing of the Nonocclusive Coronary Anastomotic Connector in an Off-Pump Porcine Bypass Model

Abstract: Objective This pilot study evaluates the anastomotic healing of the Excimer Laser Assisted Nonocclusive Anastomosis coronary connector at 6 months in a porcine off-pump coronary artery bypass (OPCAB) model. Methods Left internal thoracic artery to left anterior descending coronary artery bypass in two animals and left internal thoracic artery to left anterior descending coronary artery and right internal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…Following successful testing on large caliber arteries (3.0 mm outer diameter [OD]), this new downsized connector enables a standardized distal anastomosis (1.6 to 1.9 mm OD) for off-pump CABG (OPCAB). 6 - 8 Our previous studies demonstrated the feasibility of the ELANA Heart Bypass in OPCAB and minimally invasive direct CABG models. 9 , 10 However, follow-up data comparing the ELANA Heart Bypass to the hand-sewn, have not been provided yet.…”
Section: Introductionmentioning
confidence: 99%
“…Following successful testing on large caliber arteries (3.0 mm outer diameter [OD]), this new downsized connector enables a standardized distal anastomosis (1.6 to 1.9 mm OD) for off-pump CABG (OPCAB). 6 - 8 Our previous studies demonstrated the feasibility of the ELANA Heart Bypass in OPCAB and minimally invasive direct CABG models. 9 , 10 However, follow-up data comparing the ELANA Heart Bypass to the hand-sewn, have not been provided yet.…”
Section: Introductionmentioning
confidence: 99%
“…C = connector; RITA = right internal thoracic artery; RCA = right coronary artery. (B) A detailed SEM image at the level of the fork of the connector demonstrating complete coverage with endothelium (2,080X magnification), at 6-month followup 6,7 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…. (A) An OCT image at 6-month follow-up, transverse section, mid-anastomosis 7 . Note: the OCT wire is visible in the lumen.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations